Hearing loss and cognitive impairment among older adults: findings from the China health and retirement longitudinal study - Qin Zhao; Fei Chen; Xiaozhen Song; Yan Cai; Yue Wu; Yang Wan; Peiyuan Qiu (BMC Public Health)
Abstract Background With the rapid aging of populations, dementia has become a major health problem. Hearing loss is common among older adults and has been recognized as a contributing factor to cognitive impairment and dementia. We aimed to explore the association between hearing loss and cognitive impairment in older adults. We also sought to quantify the extent to which the impact of hearing loss on cognitive impairment could be mediated by depression and social isolation. Methods We used nationally representative data from the China Health and Retirement Longitudinal Study (CHARLS), a population-based cohort study. The study population comprised adults aged 60 and older who participated in at least two waves of the CHARLS. Cognitive function was measured based on four dimensions: orientation, computation, memory, and drawing. Hearing loss was defined according to self-reported data. We used logistic regression models to analyze the cross-sectional association between hearing loss and cognitive impairment. Cox proportional hazards models were used to examine the longitudinal association between hearing loss and cognitive impairment. We also conducted an in-depth analysis of the severity of hearing loss and its associated risk of cognitive impairment. Additionally, we calculated the percentage of excess risk mediated (PERM) by depression and social isolation. Findings In total, 7891 individuals were included in the cross-sectional analysis, and 5326 were included in the longitudinal analysis, with a mean follow-up of 6.38 years. In the cross-sectional analysis, hearing loss was associated with cognitive impairment after adjusting for all covariates (OR = 1.76, 95% CI: 1.49–2.08). In the longitudinal analysis, the hazard ratio for cognitive impairment with hearing loss compared with no hearing loss was 1.24 (95% CI: 1.06–1.46) after adjustment for demographics, socioeconomic factors, and health-related behaviors. Further analysis revealed that moderate or severe hearing loss had a strong relationship with cognitive impairment after adjusting for covariates (HR = 1.32, 95% CI: 1.07–1.62). Of the total association between hearing loss and cognitive impairment, 20.83% was mediated by depression and 4.17% by social isolation. Conclusions Hearing loss is independently associated with cognitive impairment, providing evidence that addressing hearing loss could help improve cognitive function.